Inter-Satellite Link Channel Management For Mobile Satellite Systems - Anthony Dass, Angeline (2003)
Low Earth Orbit (LEO) satellite constellations are foreseen as appropriate alternatives to the geostationary satellite systems for providing global personal communications services (PCS). Compared to geostationary satellites, these constellations offer a significantly smaller round trip delay between earth and space segments. Furthermore, the use of inter-satellite links (ISLs) has been identified as a means to provide global connectivity in space, thereby enhancing system autonomy and flexibility, and has been retained in the design of systems like Teledesic and SkyBridge. From a network point of view, a major benefit of a ISL subnetwork in space lies in the possibility to transport long distance traffic over reliable and high capacity connections, thus forming a good base for ATM (asynchronous transfer mode) operation. With the development of the third generation (3G) and fourth generation (4G) wireless networks, ATM is regarded as one of the potential promising candidates for providing QoS guaranteed broadband telecommunication services. It is possible to integrate the mobile satellite and A TM by applying the inter/intra satellite links (ISLs) as the physical layer of WATM and considering a connection between two satellites as a virtual path connection (VPC) in ATM.